Power converter for ultra low-frequency and low-voltage energy harvesters - Mikel Hualde-Otamendi; Carlos A. De La Cruz-Blas; J. Carlos Castellano-Aldave; Alfonso Carlosena (Micro and Nano Systems Letters)
Abstract Energy conversion mechanisms present in some harvesters are only able to provide very low voltage (mV) and frequency (few Hz) electrical signals, which may also have a bipolar nature (AC). These characteristics make unusable most conventional power converters to extract from them a DC voltage. This letter describes an autonomous self-starting ultra-low voltage and frequency AC-DC converter that can start the operation for AC signals around 25 mV, and below 10 Hz. The converter has been designed with ultra-low vibration harvesters in mind, but is also of application to, for instance, thermoelectric generators (TEG). The circuit is basically an oscillator driven by the harvester output, which therefore converts a low-frequency and low-voltage signal into large signal oscillation amenable for further DC conversion. The proposed circuit is based on the classical Hartley oscillator, which is modified in a nontrivial configuration, and optimized to be able to operate with bipolar, low frequency and voltage driving signals. This is achieved with a minimum number of passive components and a single JFET transistor. A practical prototype has been fabricated, and measurement results are obtained, demonstrating the feasibility of the approach. Moreover, a vibration harvester with the power converter proposed has been tested in real conditions in a wind turbine.